PERBANDINGAN DONGENG MOMOTARO (JEPANG) DAN TIMUN EMAS (INDONESIA) - Bagus Adi Ariawan, I Gusti (Humanis; Volume 8. No. 1. Juli 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Tale is a literary that has existed since ancient time. Almost every country in this world has a tale respectively, including Indonesia. Many tales in a country with other countries have same story, but have differences in delivery, figures, and cultural. One example is Momotaro tale from Japanese and Timun Emas tale from Indonesia. If examined deeper, a lot of similarities and differences will be found in these tales in terms of both function and elements of culture, including the relation to the life of the Japan and Indonesia community. This study will provide knowledge about the comparison function and cultural elements of the Momotaro tale and Timun Emas tale, as well as the relation to the daily life and culture of Japan and Indonesia community. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: comparison, function, cultural elements